Perceived Barriers to Meditation Among College Students: The Role of Personality Traits - Whitford, Samantha; Warren, Keith (Building Healthy Academic Communities Journal, 2019)
Background: Meditation is likely to be a useful intervention for anxiety and depression, and is increasingly common as a clinical intervention and informal practice among university students. However, meditation dropout rates are high, and it is likely that perceived barriers to meditation play a role. While neuroticism is known to predict dropout, there has been no study relating personality traits to these barriers. Aim: To better understand the barriers to meditation practice that university students experience. Methods: We used online survey data to analyze the relationship between personality traits, whether students practice meditation, time spent on academic and other work, and university students’ perception of barriers to meditation. Results: We found a nonlinear relationship between neuroticism and perceived barriers; the number of perceived barriers increased with increased neuroticism but eventually flattened out. Participants who meditate perceive more barriers than those who do not. We found no relationship between time spent in other activities and perception of barriers. Conclusions: Those students who would benefit most from meditation may have the most trouble continuing. Clinicians applying meditation as an intervention in a university setting should be ready to work with students on barriers to practice.